The Ineffectiveness of Dispute Resolution Through Arbitration According to Indonesian Law No. 30 of 1999 on ADR (Alternative Dispute Resolution) - Didit Wijayanto Wijaya (Journal of Law, Politic and Humanities, 2025)
This article or writing aims to find out about the ineffectiveness of settlement through arbitration according to Republic of Indonesia Law Number 30 of 1999 concerning Adr (Alternative Dispute Resolation). The problem focuses on the ineffectiveness of settlement through arbitration according to Republic of Indonesia Law Number 30 of 1999 concerning ADR (Alternative Dispute Resolution). In order to approach this problem, theoretical references from legal certainty and dispute resolution are used. The data was collected through normative legal research. The data source used is secondary data. Secondary data in this research is divided into 3 parts, including: Primary, Secondary and Tertiary Legal Materials and analyzed qualitatively.  This study concludes that arbitration is a method of resolving a civil dispute outside the general court which is based on an arbitration agreement made in writing by the parties to the dispute. However, arbitration forums also have weaknesses that both parties should consider before deciding to submit their case. Arbitration is considered to have several legal subject weaknesses in the form of states still being reluctant to give their commitment to hand over their rescue to international court bodies. The process of completing a settlement through arbitration does not guarantee that the decision will be binding.